Tumor cell-targeting radiotherapy in the treatment of glioblastoma multiforme using linear accelerators. (15th April 2021) - Chiang, Chih-Sheng; Shih, I-Ju; Shueng, Pei-Wei; Kao, Min; Zhang, Li-Wen; Chen, Shuo-Fu; Chen, Ming-Hong; Liu, Tse-Ying
Abstract: Although boron neuron capture therapy (BNCT) has enabled the delivery of stronger radiation dose to glioblastoma multiforme (GBM) cells for precision radiotherapy (RT), patients in need are almost unable to access the treatment due to insufficient operating devices. Therefore, we developed targeted sensitization-enhanced radiotherapy (TSER), a strategy that could achieve precision cell-targeted RT using common linear accelerators. TSER, which involves the combination of GoldenDisk (GD; a spherical radioenhancer), 5-aminolevulinic acid (5-ALA), low-intensity ultrasound (US), and low-dose RT, exhibited synergized radiosensitization effects. Both 5-ALA and hyaluronic-acid-immobilized GD can selectively accumulate in GBM to induce chemical and biological enhancement of radiosensitization, resulting in DNA damage, escalation of reactive oxygen species levels, and cell cycle redistribution, in turn sensitizing GBM cells to radiation under US. TSER showed an enhanced therapeutic effect and survival in the treatment of an orthotropic GBM model with only 20% of the radiation dose compared to that of a 10-Gy RT. The strategy with the potential to inhibit GBM progress and rescue the organ at risk using low-dose RT, thereby improving the quality of life of GBM patients, shedding light on achieving cell-targeted RT using universally available linear accelerators. Statement of significance: We invented GoldenDisk (GD), a radioenhancer with hyaluronic-acid (HAc)-coated gold nanoparticle (AuNP)-core/silica shell nanoparticle, to make radiotherapy (RT) safer and smarter. The surface modification of HAc and silica allows GD to target CD44-overexpressed glioblastoma multiforme (GBM) cells and stay structurally stable in cytoplasm throughout the course of RT. By combining GD with low-energy ultrasound and an FDA-approved imaging agent, 5-aminolevulinic acid (5-ALA), GBM cells were sensitized to RT leaving healthy tissues in the vicinity unaffected. The ionized radiation can further be transferred to photoelectronic products with higher cytotoxicity by GD upon collision, achieving higher therapeutic efficacy. With the newly-developed strategy, we are able to achieve low-dose precision RT with the use of only 20% radiation dose. Graphical abstract: Image, graphical abstract